Tract No. 90: An Ecumenical Opportunity from the ‘Anglican’ Newman - Emmanuel Orok Duke (Universitas Negeri Makassar, 2020)
Newman remains an ecumenical figure held in high esteem by Roman Catholics and Anglicans. His ecumenical hermeneutics is observable in Tract No. 90. This Tract is a re-reading of the Thirty-nine Articles of Religion ratified in 1571 as the fundamentals of the Anglican faith. This tract is the product of the Oxford Movement that returned to the Antiquity in view of resolving the Anglican faith crises epitomized by erastianism. This return to the Fathers of the Church had a lot of implications for the Anglican faith. Influenced by Antiquity, Newman rediscovered the common grounds between the Anglican faith and the church Catholic that inheres in the Roman Church. Thus, Tract No. 90 demonstrated that more things united the Nineteenth Anglicans and the Roman Catholics than what separated them.